Inter-strain cross-fertility tests on cultures from Israel and America in the homothallic fungus, Sordaria fimicola - B C Lamb; Z Kozlakidis; M Saleem (Fungal Genetics Reports, 2000)
Inter-strain cross-fertility was studied in relation to geographical origin in a homothallic, self-fertile fungus, by looking for hybrid perithecia in wild-type x ascospore colour mutant crosses. Strains from opposite slopes in 'Evolution Canyon', Israel, showed no cross-fertility with American or Canadian strains; there was excellent cross-fertility with other strains from the same slope, but an occasional lack of cross-fertility with strains from the other slope.